2023
DOI: 10.1101/2023.02.12.527706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient megakaryopoiesis and platelet production require phospholipid remodeling and PUFA uptake through CD36

Abstract: Lipids contribute to hematopoiesis and membrane properties and dynamics, however, little is known about the role of lipids in megakaryopoiesis. Here, a lipidomic analysis of megakaryocyte progenitors, megakaryocytes, and platelets revealed a unique lipidome progressively enriched in polyunsaturated fatty acid (PUFA)-containing phospholipids. In vitro, inhibition of both exogenous fatty acid functionalization and uptake and de novo lipogenesis impaired megakaryocyte differentiation and proplatelet production. I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…37 Barrachina et al's study underscored the significant role played by dietary polyunsaturated fatty acids and CD36 fatty acid transporters in megakaryocyte differentiation, maturation and platelet production. 38 Kong et al found that impaired bone marrow endothelial progenitor cells, characterized by reduced migration, angiogenesis, elevated reactive oxygen species levels and apoptosis, play a role in the pathogenesis of corticosteroid-resistant ITP. 4 Furthermore, atorvastatin, which regulates lipid metabolism, significantly improved the number and function of bone marrow endothelial progenitor cells in patients with corticosteroids-resistant ITP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Barrachina et al's study underscored the significant role played by dietary polyunsaturated fatty acids and CD36 fatty acid transporters in megakaryocyte differentiation, maturation and platelet production. 38 Kong et al found that impaired bone marrow endothelial progenitor cells, characterized by reduced migration, angiogenesis, elevated reactive oxygen species levels and apoptosis, play a role in the pathogenesis of corticosteroid-resistant ITP. 4 Furthermore, atorvastatin, which regulates lipid metabolism, significantly improved the number and function of bone marrow endothelial progenitor cells in patients with corticosteroids-resistant ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Barrachina et al. 's study underscored the significant role played by dietary polyunsaturated fatty acids and CD36 fatty acid transporters in megakaryocyte differentiation, maturation and platelet production 38 . Kong et al.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] A body of experimental data has demonstrated that a large amount of surface membrane necessary for proplatelet elaboration is provided by the membrane reservoir present in the megakaryocyte cytoplasm. 21,22,30,31 A variety of transgenic mice lacking F-actin-regulating proteins such as Cofilin1, Cdc42 (cell division cycle 42), and tropomodulin-3 30,32,33 or exhibiting defective lipid homeostasis such as in CD36-deficient or SR-BI (scavenger receptor class B member 1)-deficient mice 34,35 present with an aberrant DMS and concomitant defective proplatelet production and thrombocytopenia. A recent study 36 reported unaltered proplatelet production despite defective DMS formation in megakaryocytes in transgenic mice carrying a mutation within GPIbα (glycoprotein Ib-alpha) that renders it unable to bind to flnA (filamin A).…”
Section: Prerequisite For Platelet Production: Megakaryocyte Maturationmentioning
confidence: 99%
“…It has been acknowledged that severe peroxidation of membranes containing polyunsaturated fatty acids (PUFAs) is the primary driving force behind ferroptosis, which not only is regulated by lipid and iron metabolism but also involves amino acid metabolism and signaling transduction. 8 The critical steps involved in ferroptosis include intracellular free iron accumulation, glutathione depletion, and peroxidation of PUFA-rich membranes. 9 These steps are summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%